A potential prognostic marker for hematologic neoplasms: CD58 - Cao, Jiajia; Zhang, Yurong; Yue, Ningning; Xiong, Shuzhen; Zhang, Shuni; Wu, Chongyang (Frontiers in Oncology, 2025)
CD58 is a glycoprotein receptor widely distributed on histiocytes that binds to CD2, that takes part in constituting the Immunological Synapses (IS) and activating T/NK cells. Aberrant expression of CD58 has been demonstrated to exert a significant impact on the prognosis of hematological tumors, including leukemia and lymphoma. Furthermore, this aberrant expression has been associated with drug resistance and immune rejection in CAR cell therapy. In this article, we will explore the future of CD58 in hematological oncology by describing its function in immune cells, its impact on hematological oncology and immunotherapies such as CAR cell therapy.